A New Insight into the Role of Silicate-Type Binders on the Crushing Strength of Alumina Foams - Fernando de Almeida Costa Oliveira; Stéphane Pommier; Jorge Cruz Fernandes; Diamantino Dias (Crystals, 2022)
Semi-closed cell macroporous alumina foams with relative densities ranging from 0.26 to 0.35 have been produced by the well-established replication method based on the coating of a polyurethane (PU) template foam by a ceramic slurry, followed by burnout of the PU template, and sintering of the ceramic skeleton. Collapse of the three-dimensional structure upon the volatilisation of the PU sponge can only be prevented using appropriate binders. Scarce data are available on the slurry formulations of commercial alumina foams. The aim of this study was to investigate the influence of silicate-type binders, namely kaolin and bentonite additives, on the crushing strength of alumina foams. The highest crushing strength of around 10 MPa was observed at a porosity of 66 ± 2%. The open-cell model is inadequate to fit the crushing strength data of such semi-closed cell type structures. Both microscopic and macroscopic flaws resulting from the foam processing method contribute to the wide scatter of the strength, thereby explaining the Weibull modulus ranging from 4 to 7. Both flaw populations require further improvement to maximise the crushing strength of these foams with high potential for the design of structured catalyst carriers and molten aluminium filters.